Efficient method for generating homozygous embryonic stem cells in mice - Bitnara Kim; Seongjun So; Jiwan Choi; Eunju Kang; Yeonmi Lee (Journal of Animal Reproduction and Biotechnology, 2022)
Parthenogenesis is maternally uniparental reproduction through the embryonic development of oocytes without fertilization. Artificial activation of mature oocytes could generate homozygous haploid embryos with the extrusion of the second polar body. However, the haploid embryos showed low embryo development in preimplantation embryos. In this study, we investigated whether the electronic fusion of the haploid embryos could enhance embryo development and ESC establishment in mice. Haploid embryos showed the developmental delay from 4-cell to the blastocyst stage. The haploid blastomeres of the 2-cell stage were fused electronically, resulting in that the fused embryos showed a significantly higher rate of blastocysts compared to non-fused haploid embryos (55% vs. 37%). Further, the embryonic stem cells (ESCs) derived from the fused embryos were confirmed to be diploid. The rate of ESC establishment in fused embryos was significantly higher compared to non-fused ones. Based on the results, we concluded that the electronic fusion of haploid embryos could be efficient to generate homozygous ESCs.